Sepsis associated with central venous catheters in adult patients admitted to the Intensive Care Unit (Research, Society and Development, 2021)
To analyze published scientific evidence on factors for the development of sepsis associated with central venous catheters in adult patients admitted to the Intensive Care Unit. The present study is a literature review of the integrative literature review method, carried out in the months between June and November 2021. The search was carried out through the - VHL, using the Literature databases LILACS, BDENF, through - SCIELO. Adhering through the descriptors/key words: “Sepsis”, “Central venous catheter”, “Intensive Care Unit”, combined with the Boolean operator “AND”. Nosocomial infections are the main causes of death in intensive care units, representing an increase in the length of hospital stay, in addition to a high cost for institutions, by adding numerous risk factors such as: unfavorable clinical conditions, comorbidities, use of invasive techniques and changes in the microbiota. The care of critically ill patients requires the inevitable application of invasive procedures and the administration of broad-spectrum antimicrobials, so it is important that all professionals involved pay extra attention to the use of increasingly aseptic techniques, routine hand washing and the use of controlled and strictly necessary invasive techniques and antibiotics in routine care. the precise role of the nurse, through the identification of abnormal health patterns and early recognition, constitutes one of the main ways of applying nursing care, considering that, after the disease onset, the more precise and faster the actions occur. health conditions, the lower the chances of progression and severity of the disease and, consequently, the better the prognosis.